2021
DOI: 10.1038/s41438-021-00605-z
|View full text |Cite
|
Sign up to set email alerts
|

High-density linkage map construction and identification of loci regulating fruit quality traits in blueberry

Abstract: Fruit quality traits play a significant role in consumer preferences and consumption in blueberry (Vaccinium corymbosum L). The objectives of this study were to construct a high-density linkage map and to identify the underlying genetic basis of fruit quality traits in blueberry. A total of 287 F1 individuals derived from a cross between two southern highbush blueberry cultivars, ‘Reveille’ and ‘Arlen’, were phenotyped over three years (2016–2018) for fruit quality-related traits, including titratable acidity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 50 publications
4
16
1
Order By: Relevance
“…Acylation of anthocyanins is the process of adding an acyl group to the anthocyanins, which increases color stability, reduces their sensitivity to pH change, sulfite bleaching, and thermal degradation (Giusti and Wrolstad, 2003) and could be involved in bioaccessibility and bioavailability of anthocyanins (McDougall et al, 2007;Correa-Betanzo et al, 2014;Wiczkowski et al, 2016;Mengist et al, 2020a). In this study, the two major-effect loci identified on chromosomes 2 and 4 control 50% of the phenotypic variation in this mapping population.…”
Section: A Few Genes Govern Glycosylation and Acylation Of Anthocyani...mentioning
confidence: 78%
See 3 more Smart Citations
“…Acylation of anthocyanins is the process of adding an acyl group to the anthocyanins, which increases color stability, reduces their sensitivity to pH change, sulfite bleaching, and thermal degradation (Giusti and Wrolstad, 2003) and could be involved in bioaccessibility and bioavailability of anthocyanins (McDougall et al, 2007;Correa-Betanzo et al, 2014;Wiczkowski et al, 2016;Mengist et al, 2020a). In this study, the two major-effect loci identified on chromosomes 2 and 4 control 50% of the phenotypic variation in this mapping population.…”
Section: A Few Genes Govern Glycosylation and Acylation Of Anthocyani...mentioning
confidence: 78%
“…Our previous studies demonstrated that acylation and glycosylation are important variables for clustering accessions into different groups, and CHA concentration, anthocyanin concentration and profiles had a moderate to high heritability (Mengist et al, 2020a,b). Our recent study revealed that acylated anthocyanins have higher bioaccessibility than non-acylated anthocyanins (Mengist et al, 2020a), suggesting that consumption of blueberry with high acylated anthocyanin could increase absorption of these bioactives. Furthermore, acylated anthocyanins have higher color stability than the counterpart non-acylated anthocyanins, which is particularly relevant for the application of anthocyanin as a natural colorant in the food industries (Matera et al, 2015;Zhao et al, 2017;Strauch et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, in tetraploid blueberry, which is believed to exhibit polysomic inheritance (Cappai et al, 2020), previous studies succeeded in detecting genomic regions related to fruit quality, such as fruit size and scar diameter (Ferrão et al, 2018), and volatile organic compounds (Ferrão et al, 2020). In addition to GWAS, linkage map construction and quantitative trait loci (QTL) mapping have been conducted in tetraploid blueberry populations, providing novel information on the genetic regulation of fruit firmness (Cappai et al, 2020) and fruit quality (Mengist et al, 2021).…”
Section: Introductionmentioning
confidence: 99%